Implementation of the Principle of Good Faith in the Making and Execution of Agreements - Indrawati, Etty; Susilawati, Marietta D.; Putri, Koleta Donna Indhayana (West Science Law and Human Rights, 2025)
Based on Article 1338 paragraph (3) of the Civil Code, agreements must be implemented based on good faith. These guidelines must be met so that the interests of the parties can be protected and there is no risk of loss to the parties as subjects of civil law who make them. An agreement cannot be canceled by one of the parties but must be with the agreement of the parties to the agreement. The purpose of this study is to examine the difficulties that the parties have when drafting and carrying out the agreement. This study makes use of secondary data and normative legal procedures. Deductive inductive reasoning is employed. Both main and secondary legal documents are utilized. Legal tools are primary legal resources. Journal articles and other study findings are examples of secondary legal sources. qualitative approaches for data analysis. The study's findings can be used to draw conclusions about what constitutes good faith from moral and ethical perspectives in order to deal with issues that may arise if the agreement does not use good faith.